Brought To You by the Letters C, R, T, and C: Sesame Street and Canadian Nationalism - Hayday, Matthew (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2016)
The wildly popular educational program Sesame Street arrived in Canada during a key transitional period for Canadian broadcasting policy in the early 1970s. An American-made program, it was threatened with cancellation by stations seeking to meet their Canadian content (CanCon) quotas with the least possible financial cost. A heated debate that included public protests and lobbying ensued, involving the Canadian Radio-Television Commission (CRTC), the Canadian Broadcasting Corporation (CBC), the media, parliamentarians, parents and even children. Each group advanced their particular interests regarding the issue of Canadianizing television. Ultimately, the CBC provided a compromise solution with the Canadianization of Sesame Street, whereby a portion of the program’s segments would be replaced by Canadian-made material that aimed to provide messages about Canada for young children. This tumultuous debate and its ultimate solution reveal the ambivalent attitudes held by Canadians, private broadcasters, and even the CBC about both the CRTC’s Canadianization policies and the quantitative approaches used to meet its objectives. It also demonstrates the roles that activist groups and more established interests such as broadcasters have played in shaping Canadian broadcasting policy.